Upaya Menumbuhkan Literasi Digital dan Bijak Bersosial Media pada Masyarakat Desa Neglasari Kec. Limbangan Kab. Garut - Widyanti, Triani; Rohman, Slamet Nopharipaldi; Mutaqin, Ejen Jenal; Nurfitriani, Anggun (Badranaya: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service aims to provide understanding and skills for the people in Neglasari-Garut Village in cultivating digital literacy and being wise in using social media. So it is hoped that through the promotion of digital literacy, the increasingly rapid use of information technology can be handled appropriately and intelligently by the community. This service activity consists of two forms, namely socialization and training. In the first stage, namely socialization, the team presented material related to the importance of digital literacy. Then proceed with training regarding the appropriate and wise use of social media. This activity was attended by around 200 people consisting of various elements, such as village officials, community leaders, teachers and students, as well as other members of the general public. The research results showed that community service went well and smoothly, participants took part in the activity very enthusiastically and they stated that this activity was very useful in opening their minds about the importance of digital literacy and being wise in using social media.